Vasily Dokuchaev (to the 175-th anniversary) - E. A. Rusakova (Бюллетень Почвенного института им. В.В. Докучаева, 2021)
The idea of this paper is to highlight the scale of Dokuchaev's personality through the prism of readers' perception and comparison of the scientist's achievements, timed to certain milestones in his life, with their own successes. Dokuchaev's biography, filtered through his own life experience, provides a better understanding of the magnitude of the first soil scientist, and a respect for his significant scientific heritage. The work will give an insight into the extensive and varied activities of the pioneer in the comprehensive study of soils and the environment.